Joachim Breitner

Proof reuse in Coq using existential variables

Published 2018-05-18 in sections English, Coq.

This is another technical post that is only of interest only to Coq users.

TL;DR: Using existential variable for hypotheses allows you to easily refactor a complicated proof into an induction schema and the actual proofs.

Setup

As a running example, I will use a small theory of “bags”, which you can think of as lists represented as trees, to allow an O(1) append operation:

Require Import Coq.Arith.Arith.
Require Import Psatz.
Require FunInd.

(* The data type *)
Inductive Bag a : Type :=
  | Empty : Bag a
  | Unit  : a -> Bag a
  | Two   : Bag a -> Bag a -> Bag a.

Arguments Empty {_}.
Arguments Unit {_}.
Arguments Two {_}.

Fixpoint length {a} (b : Bag a) : nat :=
  match b with
  | Empty     => 0
  | Unit _    => 1
  | Two b1 b2 => length b1 + length b2
  end.

(* A smart constructor that ensures that a [Two] never
   has [Empty] as subtrees. *)
Definition two {a} (b1 b2 : Bag a) : Bag a := match b1 with
  | Empty => b2
  | _ => match b2 with | Empty => b1
                       | _ => Two b1 b2 end end.

Lemma length_two {a} (b1 b2 : Bag a) :
  length (two b1 b2) = length b1 + length b2.
Proof. destruct b1, b2; simpl; lia. Qed.

(* A first non-trivial function *)
Function take {a : Type} (n : nat) (b : Bag a) : Bag a :=
  if n =? 0
  then Empty
  else match b with
       | Empty     => b
       | Unit x    => b
       | Two b1 b2 => two (take n b1) (take (n - length b1) b2)
       end.

The theorem

The theorem that I will be looking at in this proof describes how length and take interact:

Theorem length_take''':
  forall {a} n (b : Bag a),
  length (take n b) = min n (length b).

Before I dive into it, let me point out that this example itself is too simple to warrant the techniques that I will present in this post. I have to rely on your imagination to scale this up to appreciate the effect on significantly bigger proofs.

Naive induction

How would we go about proving this lemma? Surely, induction is the way to go! And indeed, this is provable using induction (on the Bag) just fine:

Proof.
  intros.
  revert n.
  induction b; intros n.
  * simpl.
    destruct (Nat.eqb_spec n 0).
    + subst. rewrite Nat.min_0_l. reflexivity.
    + rewrite Nat.min_0_r. reflexivity.
  * simpl.
    destruct (Nat.eqb_spec n 0).
    + subst. rewrite Nat.min_0_l. reflexivity.
    + simpl. lia.
  * simpl.
    destruct (Nat.eqb_spec n 0).
    + subst. rewrite Nat.min_0_l. reflexivity.
    + simpl. rewrite length_two, IHb1, IHb2. lia.
Qed.

But there is a problem: A proof by induction on the Bag argument immediately creates three subgoals, one for each constructor. But that is not how take is defined, which first checks the value of n, independent of the constructor. This means that we have to do the case-split and the proof for the case n = 0 three times, although they are identical. It’s a one-line proof here, but imagine something bigger...

Proof by fixpoint

Can we refactor the proof to handle the case n = 0 first? Yes, but not with a simple invocation of the induction tactic. We could do well-founded induction on the length of the argument, or we can do the proof using the more primitive fix tactic. The latter is a bit hairy, you won’t know if your proof is accepted until you do Qed (or check with Guarded), but when it works it can yield some nice proofs.

Proof.
  intros a.
  fix IH 2.
  intros.
  rewrite take_equation.
  destruct (Nat.eqb_spec n 0).
  + subst n. rewrite Nat.min_0_l. reflexivity.
  + destruct b.
    * rewrite Nat.min_0_r. reflexivity.
    * simpl. lia.
    * simpl. rewrite length_two, !IH. lia.
Qed.

Nice: we eliminated the duplication of proofs!

A functional induction lemma

Again, imagine that we jumped through more hoops here ... maybe some well-founded recursion with a tricky size measure and complex proofs that the measure decreases ... or maybe you need to carry around an invariant about your arguments and you have to work hard to satisfy the assumption of the induction hypothesis.

As long as you do only one proof about take, that is fine. As soon as you do a second proof, you will notice that you have to repeat all of that, and it can easily make up most of your proof...

Wouldn’t it be nice if you can do the common parts of the proofs only once, obtain a generic proof scheme that you can use for (most) proofs about take, and then just fill in the blanks?

Incidentally, the Function command provides precisely that:

take_ind
     : forall (a : Type) (P : nat -> Bag a -> Bag a -> Prop),
       (forall (n : nat) (b : Bag a), (n =? 0) = true -> P n b Empty) ->
       (forall (n : nat) (b : Bag a), (n =? 0) = false -> b = Empty -> P n Empty b) ->
       (forall (n : nat) (b : Bag a), (n =? 0) = false -> forall x : a, b = Unit x -> P n (Unit x) b) ->
       (forall (n : nat) (b : Bag a),
        (n =? 0) = false ->
        forall b1 b2 : Bag a,
        b = Two b1 b2 ->
        P n b1 (take n b1) ->
        P (n - length b1) b2 (take (n - length b1) b2) ->
        P n (Two b1 b2) (two (take n b1) (take (n - length b1) b2))) ->
       forall (n : nat) (b : Bag a), P n b (take n b)

which is great if you can use Function (although not perfect – we’d rather see n = 0 instead of (n =? 0) = true), but often Function is not powerful enough to define the function you care about.

Extracting the scheme from a proof

We could define our own take_ind' by hand, but that is a lot of work, and we may not get it right easily, and when we change out functions, there is now this big proof statement to update.

Instead, let us use existentials, which are variables where Coq infers their type from how we use them, so we don’t have to declare them. Unfortunately, Coq does not support writing just

Lemma take_ind':
  forall (a : Type) (P : nat -> Bag a -> Bag a -> Prop),
  forall (IH1 : ?) (IH2 : ?) (IH3 : ?) (IH4 : ?),
  forall n b, P n b (take n b).

where we just leave out the type of the assumptions (Isabelle does...), but we can fake it using some generic technique.

We begin with stating an auxiliary lemma using a sigma type to say “there exist some assumption that are sufficient to show the conclusion”:

Lemma take_ind_aux:
  forall a (P : _ -> _ -> _ -> Prop),
  { Hs : Prop |
    Hs -> forall n (b : Bag a), P n b (take n b)
  }.

We use the [eexist tactic])(https://coq.inria.fr/refman/proof-engine/tactics.html#coq:tacv.eexists) (existential exists) to construct the sigma type without committing to the type of Hs yet.

Proof.
  intros a P.
  eexists.
  intros Hs.

This gives us an assumption Hs : ?Hs – note the existential type. We need four of those, which we can achieve by writing

  pose proof Hs as H1. eapply proj1 in H1. eapply proj2 in Hs.
  pose proof Hs as H2. eapply proj1 in H2. eapply proj2 in Hs.
  pose proof Hs as H3. eapply proj1 in H3. eapply proj2 in Hs.
  rename Hs into H4.

we now have this goal state:

1 subgoal
a : Type
P : nat -> Bag a -> Bag a -> Prop
H4 : ?Goal2
H1 : ?Goal
H2 : ?Goal0
H3 : ?Goal1
______________________________________(1/1)
forall (n : nat) (b : Bag a), P n b (take n b)

At this point, we start reproducing the proof of length_take: The same approach to induction, the same case splits:

  fix IH 2.
  intros.
  rewrite take_equation.
  destruct (Nat.eqb_spec n 0).
  + subst n.
    revert b.
    refine H1.
  + rename n0 into Hnot_null.
    destruct b.
    * revert n Hnot_null.
      refine H2.
    * rename a0 into x.
      revert x n Hnot_null.
      refine H3.
    * assert (IHb1 : P n b1 (take n b1)) by apply IH.
      assert (IHb2 : P (n - length b1) b2 (take (n - length b1) b2)) by apply IH.
      revert n b1 b2 Hnot_null IHb1 IHb2.
      refine H4.
Defined. (* Important *)

Inside each case, we move all relevant hypotheses into the goal using revert and refine with the corresponding assumption, thus instantiating it. In the recursive case (Two), we assert that P holds for the subterms, by induction.

It is important to end this proofs with Defined, and not Qed, as we will see later.

In a next step, we can remove the sigma type:

Definition take_ind' a P := proj2_sig (take_ind_aux a P).

The type of take_ind' is as follows:

take_ind'
     : forall (a : Type) (P : nat -> Bag a -> Bag a -> Prop),
       proj1_sig (take_ind_aux a P) ->
       forall n b, P n b (take n b)

This looks almost like an induction lemma. The assumptions of this lemma have the not very helpful type proj1_sig (take_ind_aux a P), but we can already use this to prove length_take:

Theorem length_take:
  forall {a} n (b : Bag a),
  length (take n b) = min n (length b).
Proof.
  intros a.
  intros.
  apply take_ind' with (P := fun n b r => length r = min n (length b)).
  repeat apply conj; intros.
  * rewrite Nat.min_0_l. reflexivity.
  * rewrite Nat.min_0_r. reflexivity.
  * simpl. lia.
  * simpl. rewrite length_two, IHb1, IHb2. lia.
Qed.

In this case I have to explicitly state P where I invoke take_ind', because Coq cannot figure out this instantiation on its own (it requires higher-order unification, which is undecidable and unpredictable). In other cases I had more luck.

After I apply take_ind', I have this proof goal:

______________________________________(1/1)
proj1_sig (take_ind_aux a (fun n b r => length r = min n (length b)))

which is the type that Coq inferred for Hs above. We know that this is a conjunction of a bunch of assumptions, and we can split it as such, using repeat apply conj. At this point, Coq needs to look inside take_ind_aux; this would fail if we used Qed to conclude the proof of take_ind_aux.

This gives me four goals, one for each case of take, and the remaining proofs really only deals with the specifics of length_take – no more general dealing with worrying about getting the induction right and doing the case-splitting the right way.

Also note that, very conveniently, Coq uses the same name for the induction hypotheses IHb1 and IHb2 that we used in take_ind_aux!

Making it prettier

It may be a bit confusing to have this proj1_sig in the type, especially when working in a team where others will use your induction lemma without knowing its internals. But we can resolve that, and also turn the conjunctions into normal arrows, using a bit of tactic support. This is completely generic, so if you follow this procedure, you can just copy most of that:

Lemma uncurry_and: forall {A B C}, (A /\ B -> C) -> (A -> B -> C).
Proof. intros. intuition. Qed.
Lemma under_imp:   forall {A B C}, (B -> C) -> (A -> B) -> (A -> C).
Proof. intros. intuition. Qed.
Ltac iterate n f x := lazymatch n with
  | 0 => x
  | S ?n => iterate n f uconstr:(f x)
end.
Ltac uncurryN n x :=
  let n' := eval compute in n in
  lazymatch n' with
  | 0 => x
  | S ?n => let uc := iterate n uconstr:(under_imp) uconstr:(uncurry_and) in
            let x' := uncurryN n x in
            uconstr:(uc x')
end.

With this in place, we can define our final proof scheme lemma:

Definition take_ind'' a P
  := ltac:(let x := uncurryN 3 (proj2_sig (take_ind_aux a P)) in exact x).
Opaque take_ind''.

The type of take_ind'' is now exactly what we’d wish for: All assumptions spelled out, and the n =? 0 already taken of (compare this to the take_ind provided by the Function command above):

take_ind''
     : forall (a : Type) (P : nat -> Bag a -> Bag a -> Prop),
       (forall b : Bag a, P 0 b Empty) ->
       (forall n : nat, n <> 0 -> P n Empty Empty) ->
       (forall (x : a) (n : nat), n <> 0 -> P n (Unit x) (Unit x)) ->
       (forall (n : nat) (b1 b2 : Bag a),
        n <> 0 ->
        P n b1 (take n b1) ->
        P (n - length b1) b2 (take (n - length b1) b2) ->
        P n (Two b1 b2) (two (take n b1) (take (n - length b1) b2))) ->
       forall (n : nat) (b : Bag a), P n b (take n b)

At this point we can mark take_ind'' as Opaque, to hide how we obtained this lemma.

Our proof does not change a lot; we merely no longer have to use repeat apply conj:

Theorem length_take''':
  forall {a} n (b : Bag a),
  length (take n b) = min n (length b).
Proof.
  intros a.
  intros.
  apply take_ind'' with (P := fun n b r => length r = min n (length b)); intros.
  * rewrite Nat.min_0_l. reflexivity.
  * rewrite Nat.min_0_r. reflexivity.
  * simpl. lia.
  * simpl. rewrite length_two, IHb1, IHb2. lia.
Qed.

Is it worth it?

It was in my case: Applying this trick in our ongoing work of verifying parts of the Haskell compiler GHC separated a somewhat proof into a re-usable proof scheme (go_ind), making the actual proofs (go_all_WellScopedFloats, go_res_WellScoped) much neater and to the point. It saved “only” 60 lines (if I don’t count the 20 “generic” lines above), but the pay-off will increase as I do even more proofs about this function.

Comments

Have something to say? You can post a comment by sending an e-Mail to me at <mail@joachim-breitner.de>, and I will include it here.